INTERNALIZING THE IDEAS OF ISLAMIC LAW BY ABDULLAH SYAFI'IE, THE FOUNDER OF AS-SYAFI'IYAH COLLEGE (IN THE CONTEXT OF NATIONAL LEGAL DEVELOPMENT IN INDONESIA) - Moh Zakky; Mohammad Taufik Makarao (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
This study explores the internalization of Abdullah Syafi'ie's Ideas of Islamic Law, as the founder of As-Syafi'iyah College, within the context of national legal development in Indonesia. The research aims to address two primary questions: (1) What is the historical evolution of As-Syafi'iyah College, from its establishment by Abdullah Syafi'ie and his daughter, Prof. Dr. H. Tutty Alawiyah AS, MA, to its current continuation by the third generation as its successor? (2) How has the internalization of Abdullah Syafi'ie's Ideas of Islamic Law, as the founder of As-Syafi'iyah College, impacted the fields of Islamic Studies, Social Sciences, and Education within the broader context of national legal development in Indonesia?. In conclusion, the history of As-Syafi'iyah College, established by KH. Abdullah Syafi'ie and Prof. Dr. H. Tutty Alawiyah AS, MA, has undergone a lengthy and transformative journey spanning from 1933 to the present day. The institution's legacy is now carried forward by successors, including Prof. Dr. Dailami Firdaus, SH, LLM, MBA, and Dr. Syifa Fauzia, MA. The internalization of Abdullah Syafi'ie's Ideas of Islamic Law within the context of national legal development is an integral part of the college's daily activities. It is worth noting that while Abdullah Syafi'ie himself was not directly involved in drafting legislation related to marriage, criminal offenses (such as gambling and adultery), education, social issues, and waqf, his practices and activities served as a source of inspiration for the formulation of various legislative regulations in these areas.